2021
DOI: 10.1002/admt.202001184
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Multifunctional Detection of Th4+ and UO22+ in the Post‐Synthetically Modified Metal–Organic Framework and Application of Functional MOF Membrane

Abstract: The field of post‐synthesis modification has aroused widespread concern from diverse perspectives, including chemistry, biology, and material science. Post‐synthesis modification can introduce rich functionality into metal–organic frameworks (MOFs) without destroying the main structure of MOFs. Based on this research status, a series of lanthanide metal–organic frameworks ([Ln2(NH2‐BDC)2.5(CH3COO)(DMA)(H2O)]•DMA, Ln = Pr, Nd, Sm, Eu, Gd and Tb, NH2‐BDC = 2‐aminoterephthalic acid, DMA = N,N‐Dimethylacetamide) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…The sensing mechanism indicated that the competitive absorption of the excitation light significantly contributed to the luminescence quenching, whereas the high uptake and sensing capacity toward Th 4+ were mainly caused by host-guest interaction. In 2021, Li et al proposed a series of 3D LMOFs, [Ln 2 (NH 2 -BDC) 2.5 (CH 3 COO)(DMA)(H 2 O)]·DMA, Ln = Pr, Nd, Sm, Eu, Gd, and Tb, NH 2 -BDC = 2-aminoterephthalic acid, DMA = N,N -Dimethylacetamide) by hydrothermal synthesis, as shown in Figure 13 a [ 96 ]. A series of post-synthesis modified materials with great fluorescence and quite stable structure were finally synthesized by an aldimine reaction, due to the existence of uncoordinated amino groups in the organic ligands.…”
Section: Lmofs For Hazardous Materials Detectingmentioning
confidence: 99%
“…The sensing mechanism indicated that the competitive absorption of the excitation light significantly contributed to the luminescence quenching, whereas the high uptake and sensing capacity toward Th 4+ were mainly caused by host-guest interaction. In 2021, Li et al proposed a series of 3D LMOFs, [Ln 2 (NH 2 -BDC) 2.5 (CH 3 COO)(DMA)(H 2 O)]·DMA, Ln = Pr, Nd, Sm, Eu, Gd, and Tb, NH 2 -BDC = 2-aminoterephthalic acid, DMA = N,N -Dimethylacetamide) by hydrothermal synthesis, as shown in Figure 13 a [ 96 ]. A series of post-synthesis modified materials with great fluorescence and quite stable structure were finally synthesized by an aldimine reaction, due to the existence of uncoordinated amino groups in the organic ligands.…”
Section: Lmofs For Hazardous Materials Detectingmentioning
confidence: 99%
“…We select compound 1 to detect three aldehyde vapors (salicylic aldehyde, furfural, and benzaldehyde). In order to detect aldehydes vapors speedily, we have prepared a homemade equipment . First, we put the double-sided tape on the appropriate position of the quartz plate, and then evenly smear compound 1 powder on the double-sided tape.…”
Section: Resultsmentioning
confidence: 99%
“…In order to detect aldehydes vapors speedily, we have prepared a homemade equipment. 44 First, we put the double-sided tape on the appropriate position of the quartz plate, and then evenly smear compound 1 powder on the double-sided tape. The quartz plate was placed into the cuvette, and then 20 μL of aldehyde compounds were dropped into the cuvette.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The single-crystal diffraction results showed that the red crystals were the title compounds, while the pale yellow ones were the compounds reported in the literature. [32] Due to the introduction of the chromophore pbpyCl 2 moiety, we suspected that addition of pbpyCl 2 was responsible for the reason of the corresponding two compound crystals. First, we changed the amount of pbpyCl 2 , other things being equal.…”
Section: Key Conditions Of Crystallizationmentioning
confidence: 99%
“…In previous work, we successfully synthesized MOFs by using NH 2 -BDC and lanthanide metal salts. [32] In this work, we attempted to embed the chromophore pbpy moieties into MOF channels or coordinate with rare earths to alter the fluorescence properties. However, the synthesis process was not as smooth as expected.…”
Section: Key Conditions Of Crystallizationmentioning
confidence: 99%